Long-time Behavior for the Navier-Stokes-Voight Equations with Delay on a Non-smooth Domain (Journal of Partial Differential Equations, 2018)
This paper concerns the long-time behavior for the 2D incompressible Navier-Stokes-Voightequations with distributed delay on a non-smooth domain. Under someassumptions on the initial datum and the delay datum, the existence of compact globalattractors is obtained.
Keywords: Navier-Stokes-Voight equations; distributed delay; global attractors.